PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK ETIKA DIGITAL SISWA SD DI ERA MEDIA SOSIAL - Dewi Dewi Malika Yuliani; Khoerunnisa; Diar Puspita Maryam; Regina Selvi Natasya (STKIP Subang, 2025)
The development of information and communication technology has brought significant changes to society, including in education. Increased use of social media among elementary school students facilitates interaction but also poses digital ethics challenges. Many cases of misuse, such as hoaxes and cyberbullying, show the urgency of digital ethics education from an early age. Civics Education (PKn) has a strategic role in instilling moral values, including those needed in digital contexts. This study used a qualitative case study method involving 5th and 6th-grade students in Jakarta. Data collection included observations, teacher interviews, and document analysis. Results show that although PKn can shape responsible digital citizens, its integration with digital ethics remains limited. The study recommends updating curriculum and teacher training to align PKn with current digital challenges.